2019
DOI: 10.1101/586768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuroanatomical Correlates in Bilinguals: The Case of Children and Elderly

Abstract: How bilingualism modulates brain areas beyond the language regions is still controversial. Through a comprehensive set of analyses on brain structure, we investigated brain differences between Basque-Spanish bilinguals and monolinguals in children and the elderly, the most sensitive target groups to detect potential brain differences. In particular, we employed Diffusion MRI in combination with T1-MRI, network-based statistics and a graphtheoretical approach to investigate differences between bilinguals and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 87 publications
(124 reference statements)
0
16
0
Order By: Relevance
“…It is important to note that we did not exclude studies for age range of participants or L1/L2 language (other than bimodal bilinguals as noted above), as there are not enough studies fitting the criteria to investigate consistency within specific age ranges (see below). It is also worth stating that we included García-Pentón et al (2019), which at the time was a preprint available on bioRxiv (https://www.biorxiv.org/). The methodology was determined to be of the quality of the other studies found, and as it met all of the inclusion criteria it was determined appropriate to include in the final meta-analyses conducted here.…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…It is important to note that we did not exclude studies for age range of participants or L1/L2 language (other than bimodal bilinguals as noted above), as there are not enough studies fitting the criteria to investigate consistency within specific age ranges (see below). It is also worth stating that we included García-Pentón et al (2019), which at the time was a preprint available on bioRxiv (https://www.biorxiv.org/). The methodology was determined to be of the quality of the other studies found, and as it met all of the inclusion criteria it was determined appropriate to include in the final meta-analyses conducted here.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Foci from monolingual > bilingual contrasts were only reported for one of the eight studies (Olulade et al, 2016), so only the bilingual > monolingual contrast analyses were run and reported here. Out of the ten eligible comparisons, two included separate age groups with unique contrasts eligible for inclusion: older and younger adults (Gold et al, 2013), and adults and children (García-Pentón et al, 2019). The later study was the only study included that contained children.…”
Section: Description Of Eligible Studiesmentioning
confidence: 99%
See 3 more Smart Citations